Inhibition of CYP2E1 and activation of Nrf2 signaling pathways by a fraction from Entada africana alleviate carbon tetrachloride-induced hepatotoxicity. Issue 8 (August 2020) - Kouam, Arnaud Fondjo; Owona, Brice Ayissi; Fifen, Rodrigue; Njayou, Frédéric Nico; Moundipa, Paul Fewou
Abstract: Entada africana is used in non-conventional medicine for the management of liver ailments. A fraction, designated EaF10 (methylene chloride/methanol 90:10, v/v) with promising hepatoprotective activity has been isolated. Since the mechanisms underlying EaF10 hepatoprotective action remain unknown, this study was undertaken to investigate the anti-hepatotoxic mechanism of the fraction against carbon tetrachloride (CCl4 )-induced hepatotoxicity and its antioxidant properties. Antioxidant activities of EaF10 were assessed through four chemical antioxidant assays and its anti-hepatotoxic effect evaluated in vivo and in vitro by post-treatment (25 or 100 mg/Kg) or co-treatment (6.25–100 μg/mL) in CCl4 -intoxicated mice and normal human liver cells line L-02 hepatocytes respectively; and biochemical and molecular parameters assessed respectively by spectrophotometry, and by quantitative real-time polymerase chain reaction and western blot analysis. EaF10 exhibited strong antioxidant activities correlated with its polyphenol content. Serum levels of alanine/aspartate aminotransferase (AST/ALT) and nitrite oxide, liver contents of glutathione (GSH) protein carbonylation and malondialdehyde (MDA), liver activities of catalase (CAT), glutathione-S-transferase (GST) and superoxide dismutase (SOD) and cell viability showed the anti-hepatotoxic effect of EaF10, supported by histopathological observations. The fraction decreased the protein level of Cytochrome P450 2E1 (CYP2E1) and Kelch-like ECH-associated protein-1 (Keap-1), induced nuclear translocation of Nuclear factor-erythroid 2-related factor-2 (Nrf2) coupled to an increase of the mRNA levels of CAT, SOD1 and GST in CCl4 -intoxicated L-02 hepatocytes. These findings evidenced that the studied plant fraction possesses a strong antioxidant capacity and prevents CCl4 -induced hepatotoxicity, likely through inhibition of CYP2E1 and activation of the Nrf2 signaling pathway. Abstract : Entada africana ; Fraction EaF10; Carbon tetrachloride; Anti-hepatotoxic; CYP2E1; Nrf2; Natural product chemistry; Pharmaceutical chemistry; Pharmaceutical science; Biochemistry; Molecular biology; Toxicology